(untitled) (Bulletin of Innovative Research, 2026)
The article analyzes the types of speech influence from the perspective of illocutionary speech acts. The classifications proposed by L. Fedorova and Y. Shelestyuk are presented and explained with examples taken from Uzbek, English, and Russian.